Presenting methodological resilience for conducting research with vulnerable populations during current and future pandemics: a case study with IPV shelters and survivors in the United States - Ravi, Kristen E. (Journal of family violence, 2024)
Purpose: In this brief report, we highlight the challenges that we experienced while attempting to conduct primary data collection with intimate partner violence (IPV) survivors living in an IPV emergency shelter throughout the prolonged COVID-19 pandemic and our strategies to overcome them. Method: In the summer of 2021, we began collecting data on a study investigating maternal-child bonding while living in IPV emergency shelters. We proposed a 14-day electronic daily diary methodology with follow-up semi-structured interview. The purpose of the study was to understand what factors affect maternal-child bonding to support survivors’ relationships with their children while living in an emergency shelter. Results: We encountered two global obstacles to study implementation: the Institutional Review Board (IRB) pausing in-person data collection and low IPV shelter utilization. In what we term methodological resilience, we engaged in innovative and flexible team work to overcome these barriers. Specific strategies centered on creating an entirely remote data collection process and expanding our geographic area and participant eligibility criteria. Conclusions: Implications for researchers include greater communication with IRB offices, planning for multi-state recruitment, triangulated recruitment methods, reminder texts for participants and incremental incentives to ensure continued engagement with the study.